2010
DOI: 10.1254/jphs.10181fp
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Ceramidase and Ceramide Kinase by Vanadate via a Tyrosine Kinase–Mediated Pathway

Abstract: Abstract. Ceramide, a key molecule in the metabolism of sphingolipids, is converted by ceramidase to sphingosine, and phosphorylated by ceramide kinase to form ceramide-1-phosphate (C1P). In this study, we improved on a method of thin-layer chromatography using a fluorescent ceramide, 4-nitrobenzo-2-oxa-1,3-diazole-labeled C6-ceramide (NBD-ceramide) by adding another step for separation of extracted ceramide metabolites by lipophilicity, and determined levels of C1P, caproic acid, sphingomyelin, and glucosylce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 49 publications
(64 reference statements)
2
28
0
Order By: Relevance
“…NBD-labeled ceramide metabolites including NBD-C1P were separated using TLC, and the levels of metabolites were determined as described previously. 14,26,27) Absolute values (pmol/well) of ceramide metabolites in HepG2 cells were similar to those in cells previously reported, 14,26,27) and the relative levels of NBD-sphingomyelin, NBD-glucosylceramide, and NBD-C1P at 30 min after labeling with NBD-ceramide were 5-10 (% of NBD-ceramide), 3-6, and 0.05-0.1%, respectively. Since the ceramide metabolites showed a wide range of values and the absolute values varied depending on experiments, the data in Figs.…”
Section: Measurement Of Nbd-c1p Formation In Hepg2 Cellssupporting
confidence: 89%
See 1 more Smart Citation
“…NBD-labeled ceramide metabolites including NBD-C1P were separated using TLC, and the levels of metabolites were determined as described previously. 14,26,27) Absolute values (pmol/well) of ceramide metabolites in HepG2 cells were similar to those in cells previously reported, 14,26,27) and the relative levels of NBD-sphingomyelin, NBD-glucosylceramide, and NBD-C1P at 30 min after labeling with NBD-ceramide were 5-10 (% of NBD-ceramide), 3-6, and 0.05-0.1%, respectively. Since the ceramide metabolites showed a wide range of values and the absolute values varied depending on experiments, the data in Figs.…”
Section: Measurement Of Nbd-c1p Formation In Hepg2 Cellssupporting
confidence: 89%
“…13) Previously, we reported that treatment with orthovanadate, a general inhibitor of tyrosine phosphatase, increased C1P formation via CerK in A549 cells and CHO cells. 14) However, precise mechanisms for the posttranslational regulation of CerK activity have not yet been elucidated.…”
mentioning
confidence: 99%
“…GA and 17-AAG were used at concentrations reported previously (Sano, 2001;Salehi et al, 2006;Clark et al, 2009). The concentrations of other reagents were also the same as those in previous reports (Taniguchi et al, 2007;Kurosawa et al, 2009;Tada et al, 2010). GA, 17-AAG, PMA, and A23187 were dissolved in dimethyl sulfoxide.…”
Section: Methodsmentioning
confidence: 99%
“…The labeled cells were washed twice with NBD-ceramide-free medium and further incubated for 1 hr with Na 3 VO 4 . Lipid extraction was performed using a chloroform/methanol solution followed by vigorous vortex mixing, and the lipids in the organic and aqueous phases were analyzed on a TLC silica gel 60 plate (#105724, Merck, German) using 1-butanol: acetic acid: water (3:1:1) as the mobile phase, as described (Tada et al, 2010) with minor modifications. The fluorescence was detected with LAS1000-Plus (Fuji-Film, Tokyo, Japan; 470 nm excitation and 515 nm emission).…”
Section: Measurement Of Ceramide Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation